Perineal repair of a full‐thickness rectal prolapse in a wild Sumatran orangutan (Pongo abelii). Issue 1 (11th October 2018) - Saraswati, Yenny; Sedman, Peter; Sedman, Rebecca; Wibisono, Andika Pandu; Nente, Citrakasih; Simatupang, Meuthya Sr; Singleton, Ian; Pizzi, Romain
Abstract: A Delorme's procedure perineal surgical repair was performed in a wild adult male Sumatran orangutan ( Pongo abelii ) with a chronic persistent rectal prolapse that had been unsuccessfully treated by 6 previous surgeries. The rectal prolapse did not recur, and the orangutan was successfully released to the wild, 6 weeks later.